Effects of Yangxinshi tablet on exercise tolerance in patients with coronary heart disease: A protocol of randomized, double-blind, placebo-controlled, and multi-center trial. Issue 31 (31st July 2020) - Zhang, Sisi; Liang, Congying; Yang, Yang; Zhao, Zhijia; Li, Jiaojiao; Meng, Xiaoping
Abstract: Background: Exercise intolerance is very common in patients with coronary heart disease (CHD). Although some researches confirming the validation of traditional Chinese medicine (TCM) on CHD treatment, the effect of TCM on improving the exercise tolerance of patients with CHD remains unclear so far. Our trial is to investigate whether the Yangxinshi (YXS) tablet can improve exercise tolerance as well as the quality of life among CHD patients. Methods: It is a randomized, double-blind, placebo-controlled, multi-center trial. A total of 90 patients with CHD from 3 hospitals in China will be enrolled and randomly assigned to one of 2 groups: YXS group, N = 45; placebo group, N = 45. The 2 groups will simultaneously receive standardized western medicine and exercise-based cardiac rehabilitation program for 12 weeks. The primary outcome measure is the exercise capacity, which will be evaluated by the cardiopulmonary exercise test and 6-minute walking test. The 2nd outcomes include symptom improvement, psychologic issues, laboratory tests, side effects, and adverse events. Discussion: To our knowledge, it is the 1st randomized controlled trial to evaluate the effect of TCM YXS tablet on exercise tolerance in patients with CHD. The results will provide more evidence for future studies in this area. Trial registration: This study protocol was registered in Research Registry (researchregistry5752).